A Multiyear Assessment of Public Response to a Statewide Drug Take-Back and Disposal Campaign, 2010 to 2012. (August 2017) - Yanovitzky, Itzhak
This study is the first to analyze public response to a drug take-back program, the American Medicine Chest Challenge, in a single state over a period of 3 years (2010-2012). The study utilized a three-wave repeated cross-sectional design and an annual phone survey conducted with a representative sample of adults ( N = 906 in 2010, N = 907 in 2011, and N = 906 in 2012), which assessed exposure to the campaign, drug disposal behaviors, possible mediators of campaign effects (risk appraisal, personal agency, normative influence, and interpersonal talk), and potential confounders. Logistic regression and causal mediation analysis were employed to estimate confounder-adjusted direct and mediated effects of the campaign. Results showed that the campaign reached a sizable portion (50% to 60%) of state adults and that campaign exposure was associated with increased likelihood of having conversations with others about this topic. About 55% of all adults in the state reported taking at least one of the actions recommended by the campaign, and campaign exposure was associated with increased likelihood of disposing of prescription drugs at a drug collection day event (adjusted odds ratio = 4) and of talking to a child about the risks associated with prescription drug abuse (adjusted odds ratio = 2). The causal mediation analysis demonstrated that the campaign influenced audiences by reinforcing their efficacy to safely dispose of prescription drugs, but also potentially by stimulating conversations among community members about this topic. Drug take-back campaigns can be an effective mechanism to decrease the availability of prescription drugs in communities.